Associação da ocorrência do Ectima Contagioso (Orf vírus) em ovinos com seus cuidadores - Ferreira, Bruna Lapenna Sanches [UNESP] (2015)
Responsible for significant economic losses in affected flocks, the Contagious Ecthyma is a disease caused by Orf virus belonging to the genus Parapoxvirus, epitheliotropic, the Poxviridae family and subfamily Chordopoxvirinae. It could be transmitted to humans who handle and work with infected sheep, causing crusted lesions and proliferative skin and the mucocutaneous junction, both in animals and in humans. The study showed the disease diffusion in São Paulo. They sampled 42 (8.64%) Animal caregivers and 444 (91.36%) sheep (n = 486). Of these, 453 (93.21%) showed no clinical signs, while 33 (6.79%) suspected cases of the disease (32 sheep and a caregiver) that were biopsied and performed histopathological and PCR tests. This all samples (n = 486) were suggestive of Ecthyma Contagious 6.38% and 0.41% suggestive of other skin lesions on histopathological examination. In examining PCR among 486 sampled, 4.32% were positive, while 2.47% were negative. The prevalence of reagents for virus neutralization was 67% in sheep and their caregivers 76% (p = 0.22). The distribution of titles had statistically significant differences between species with p = 0.0048. All surveyed 486 samples were negative in PCR test blood. The prevalence of animals with crust resulted in 7.2% and 2.4% their caregivers. Statistical analyzes were performed with SAS software (SAS Institute, 2011) at 0.05 significance level. Virus neutralization test in conclusion serum between species was statistically significant (p = 0.048), therefore, it is suggested that the higher the coexistence of sheep with their caregivers; the correlation between the diagnostic methods of virus neutralization, PCR and histopathology are important associations for the conclusive diagnosis of the disease; the disease is widespread in São Paulo and the geographical distribution did not influence the genetic similarity of the virus